Sweden's COVID-19 Recession: How Foreign and Domestic Infections Struck against Firms and Workers - Anders Akerman; Karolina Ekholm; Torsten Persson; Oskar Nordström Skans (Institute of Labor Economics (IZA), 2022)
Using highly granular micro data, we document very divergent economic effects of the COVID-19 pandemic on Swedish private-sector firms and their workers. Firms that exported to, or imported from, heavily afflicted countries reduced their output due to disrupted trade. Service firms that operated in locations with many infections reduced their output due to falling local consumption, despite very limited regional restrictions. Workers at the bottom of each social gradient – defined by education, earnings or ethnicity – took a twofold hit: their employers faced the largest output drops and they experienced the largest transmissions from firm output to earnings.
Keywords: J23; J31; 330; COVID-19; virus transmission; inequality